Upaya Peningkatan Pengetahuan Ibu Hamil Dengan Penyuluhan Kesehatan Pregnancy Massage Untuk Mengatasi Kualitas Tidur Ibu Hamil Trimester III - Amelia Nur Hidayanti; Nurmupida Abbas; Luluk Yuliati; Agriyaningsih Oktaviana (JURNAL PENGABDIAN KADER BANGSA, 2026)
Sleep disturbances are among the most common complaints experienced by women during the third trimester of pregnancy due to physiological and psychological changes. One non-pharmacological intervention that may help improve sleep quality during pregnancy is pregnancy massage. This community service activity aimed to improve the knowledge and skills of third-trimester pregnant women regarding pregnancy massage as an effort to reduce pregnancy-related discomfort and support better sleep quality. The activity was conducted on May 16, 2026, at TPMB Jamilah, Pesanggrahan District, South Jakarta, involving 12 third-trimester pregnant women. The methods included health education, demonstrations, hands-on practice, discussions, and evaluation. The results showed that 90% of participants were able to explain the definition, benefits, and techniques of pregnancy massage after the educational session. In addition, 85% of participants were able to correctly demonstrate the massage techniques. Participants showed a high level of enthusiasm, reflected by their active involvement in discussions, question-and-answer sessions, and practical activities. In conclusion, the program successfully improved participants’ knowledge and skills regarding pregnancy massage and increased their understanding of its benefits in enhancing comfort and sleep quality during pregnancy.